After Cloven Tongues of Fire : Protestant Liberalism in Modern American History - Hollinger, David A. (Princeton University Press, 2013)
The role of liberalized, ecumenical Protestantism in American history has too often been obscured by the more flamboyant and orthodox versions of the faith that oppose evolution, embrace narrow conceptions of family values, and continue to insist that the United States should be understood as a Christian nation. In this book, one of our preeminent scholars of American intellectual history examines how liberal Protestant thinkers struggled to embrace modernity, even at the cost of yielding much of the symbolic capital of Christianity to more conservative, evangelical communities of faith.</p.